Differential climate change vulnerability among different poverty groups in southwestern Bangladesh: lessons for adaptation planning - Ha-Mim, N.M; Hossain, M.Z. (Recent Research in Science and Technology, 2020)
This article draws on research findings from fieldwork undertaken in Mongla Upazila of Southwest Bangladesh from 2018 to 2019 to analyse how climate-related vulnerability and adaptation is differentiated among different poverty groups. The principal aim of this research is to investigate complex relationship between vulnerability, poverty, and adaptation in a case study carried out in two rural cyclone-prone areas of southwest Bangladesh, focusing on household level vulnerability and adaptive responses to climate change. The quantitative research strategy was adopted in this research. Specific methods utilized for the data collection process included in-depth questionnaire survey of 98 households. The significance of the results was in the differences of poverty and adaptation choices of the households with differential climate change vulnerability which revealed a complex relationship within vulnerability, poverty and adaptation. This research also highlighted that the poor households with high vulnerability could highly be adaptive through adopting a significant number of adaptations to deal with sudden and gradual changes in climate, but the results also suggest that households who are not poor who have usually low vulnerability, likely to have less adaptive responses than households who have high vulnerability. Moreover, this research is an attempt to reveal the complex relationship among vulnerability, poverty and adaptation that may help to develop more effective adaptation framework than before to deal with climate variability and change.